SARS-CoV-2 antibody responses post-vaccination in UK healthcare workers with pre-existing medical conditions: a cohort study. Issue 12 (1st December 2022) - Ward, Victoria; Wei, Jia; Gordon, William; Barnes, Eleanor; Dunachie, Susie; Jeffery, Katie; Eyre, David; O'Donnell, Anne-Marie
Abstract : Objectives: To examine antibody responses after the second vaccination in healthcare workers (HCWs) with underlying health conditions. Design: Cohort study. Setting: Oxford University Hospitals in the United Kingdom. Participants: Healthcare workers who had SARS-CoV-2 serological data available and received two SARS-CoV- 2 vaccinations. Primary outcome: Peak SARS-CoV-2 anti-spike IgG responses after the second vaccination and associations with underlying health conditions and the estimated risk of severe COVID-19 using an occupational health risk assessment tool. Methods: We used univariable and multivariable linear regression models to investigate associations between antibody levels and demographics (age, sex, ethnicity), healthcare role, body mass index, underlying health conditions, vaccination status, prior infection and the Association of Local Authority Medical Advisors COVID-age risk score. Results: 1635 HCWs had anti-spike IgG measurements 14–84 days after second vaccination and data on any underlying health conditions. Only five HCWs (0.3%), all on immunosuppressive treatment, (including four organ transplant recipients), did not seroconvert after second vaccination. Antibody levels were independently lower with older age, diabetes, immunosuppression, respiratory disorders other than asthma and markedly so in organ transplant recipients. Levels were independently lower in ChAdOx1 versus BNT162b2 recipients and higher following previous infection. HCWs with 'very high' COVID-age risk scores had lower median antibody levels than those with 'low', 'medium' or 'high' risk scores; 4379 AU/mL, compared with 12 337 AU/mL, 9430 AU/mL and 10 524 AU/mL, respectively. Conclusions: Two vaccine doses are effective in generating antibody responses among HCWs, including those with a high occupational risk. However, HCWs with underlying health conditions, especially diabetes, immunosuppression and organ transplant, had lower antibody levels, and vaccine response monitoring may be needed.